(3Odjd GdWGdH aj GdeMGSHI (B:s 280 (3SDGd h LhGH (B/s - (3LYGQI, CSGeI YeQs ((3YeGf(B: s (3OGQ hGFd(B, s, 2008)
(3GdeMGSHI aj HjFI GdYed , YedjI GdJSLjd , JShjI GdMSGHGJ , GSJceGd GdOhQI GdeMGSHjI , GdeMGSHI aj YedjGJ GdHVGYI , GdeMGSHI Yf GdeNRhf , fXe eYdheGJ eMGSHjI , GdQbGHI GdOGNdjI h GdfbOjI , GdeMGSHI Yf GdeOjfhf GdYbGQGJ h GdeYOGJ , GdNehGQO GdWHjYjI h GdGUhd ZjQ GdedehSI , GdGdJhGeGJ bUjQI GdGLd heMGSHI GdGLhQ h GdQhGJH , GdeHGOF GdeMGSHjI , GdeMGSHI Yf TQcGJ GdGTNGU (B((3GdJVGef(B) (3, TQcGJ GdGehGd(B( (3GdeSGgeI (B) : (3GdJfXjeGJ h YedjGJ QCS eGd GdGSge , TQcGJ GdGehGd (B( (3GdSGgeI (B): (3GdJGhRjYGJ , GdGQHGM GdeMJLRI h GdJbQjQ Yf GdONd(B.s
Keywords: (3GdeMGSHIs; (3eMGSHI GdTQcGJs